2015
DOI: 10.1097/j.pain.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurochemical analysis of ongoing bone cancer pain in rats

Abstract: Cancer-induced bone pain is described as dull, aching ongoing pain. Ongoing bone cancer pain was characterized following intratibial injection of breast cancer cells in rats. Cancer produced time-dependent bone remodeling and tactile hypersensitivity but no spontaneous flinching. Conditioned place preference (CPP) and enhanced dopamine (DA) release in the nucleus accumbens shell (NAc) was observed following peripheral nerve block (PNB) selectively in tumor-bearing rats revealing nociceptive driven ongoing pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 55 publications
4
45
2
Order By: Relevance
“…Our laboratory has evaluated pain motivated behavior and demonstrated that relief of ongoing pain is a natural reward that evokes DA release within the NAc [22; 59], consistent with human imaging studies [6; 7; 24; 62; 93]. We proposed that release of dopamine in the NAc by intrinsically non-rewarding treatments in the setting of injury could represent a translational biomarker of pain relief [24; 62; 69; 93]. In the present study, our data show that R9-CBD3-A6K reverses evoked hypersensitivity in nerve-injured rats.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our laboratory has evaluated pain motivated behavior and demonstrated that relief of ongoing pain is a natural reward that evokes DA release within the NAc [22; 59], consistent with human imaging studies [6; 7; 24; 62; 93]. We proposed that release of dopamine in the NAc by intrinsically non-rewarding treatments in the setting of injury could represent a translational biomarker of pain relief [24; 62; 69; 93]. In the present study, our data show that R9-CBD3-A6K reverses evoked hypersensitivity in nerve-injured rats.…”
Section: Discussionmentioning
confidence: 70%
“…We previously demonstrated that pairing a context with a treatment that effectively relieves ongoing pain produces preference for that context (i.e., conditioned place preference) through negative reinforcement. Removal of aversive states induced by ongoing pain by intrinsically non-rewarding treatments (e.g., peripheral nerve block with lidocaine or intravenous ketorolac [62; 69; 93]) are accompanied by release of dopamine in the nucleus accumbens (NAc) shell representing the natural reward of pain relief. Thus, assessment of NAc dopamine release was proposed as an objective, neurochemical translational biomarker of pain relief [24; 62; 69; 93]; this concept has been validated in post-surgical [61], cephalic [24], osteoarthritic [64], neuropathic [93], and cancer-induced bone [69] pain.…”
Section: Introductionmentioning
confidence: 99%
“…CPP is dependent on the reward system. The enhanced dopamine (DA) released in the nucleus accumbens (NAc) shell was related to CPP in rats with tumor 27 or spinal nerve ligation (SNL). 28 Pharmacologic activation of the rACC opioid receptors of injured animals was sufficient to stimulate dopamine release in the NAc and produce CPP.…”
Section: Discussionmentioning
confidence: 99%
“…Associative relief learning is revealed by motivation to seek that context in the future. We and others have demonstrated CPP with pain relieving treatments in multiple experimental pain models including: neuropathic (SNL, spinal nerve injury; SNI, partial or complete axotomy, spinal cord lesions, cisplatin-induced polyneuropathy) (62-65), inflammatory (Complete Freund's Adjuvant, CFA) (66, 67), post-surgical (incisional) (68), bone cancer (69) and osteoarthritic (mono-iodoacetate, MIA) (70, 71) pain. Importantly, treatments that are not intrinsically rewarding but alleviate pain in humans (e.g., lidocaine-induced peripheral nerve blockade or intrathecal administration of ω-conotoxin (ziconotide) (72) or clonidine (73, 74) do not produce CPP in uninjured animals but can do so in the presence of ongoing pain.…”
Section: Nucleus Accumbens Dopamine Signaling and Relief Of Ongoing Painmentioning
confidence: 99%